Barriers analysis for green supply chain management implementation in power industry using ISM. Issue 2 (2017) - Soda, Sheetal; Sachdeva, Anish; Garg, Rajiv Kumar
The Indian power industry is witnessing a phase of transition, wherein switchover from traditional operations to modern practices is precipitating; but still there is a long way to go. This research paper makes an attempt to assess the barriers that were identified from extensive literature review and opinions invited from power industry-experts that impede implementation of green supply chain management by making use of interpretive structural modelling (ISM). Out of 16 barriers, insufficient government support and limited investment in green measures barriers are found to be significant, which invoke unfavourable response from the government. To enhance the validity of the results so reached, opinions of different industry experts were invited to corroborate the earlier deductions; thereby yielding a more accurate model. This has added to the credibility of the findings.